Sociodemographic and travel characteristics affecting the purpose of selecting Bangkok as a tourist destination. (April 2018) - Suttikun, Chompoonut; Chang, Hyo Jung; Acho, C. Stephanie; Ubi, McDaniel; Bicksler, Hamilton; Komolsevin, Rosechongporn; Chongsithiphol, Srisuda
Bangkok, Thailand is in a unique position to benefit economically and has become one of the world's most popular tourist destinations, due to its function as a hub for international travel in Southeast Asia. Thus, this study examines how past experiences, age, income, gender, education level, occupation, and regions affect international tourists' reasons to visit Bangkok. After conducting chi-square analysis on 400 participants, significant differences were found among the varying income levels, occupations, education levels, and regions of origin and their reasons for visiting Bangkok. However, no significant differences were found based on age and gender regarding reasons to visit Bangkok. As far as regions of origin, Europeans were most likely to visit Bangkok as a stopover in route to another destination. This lays the foundations for further research focusing on what Bangkok can do to increase their status as a destination for European travelers.